The Analysis of Student Character Values in the Use of Secondary Metabolic Utilization Lab Module - Nurhafidhah, Nurhafidhah; Hasby, Hasby; Alvina, Sirry (SCAD Independent, 2021)
The values ​​of character in the classroom can be applied through practical activities. Therefore, the learning needs to be applied using lab modules that foster student character values. The purpose of this study was to describe the value of independent character, Environmental Awareness, and curiosity of students on the application of the lab module for the use of secondary metabolites. The research was a descriptive study. It was conducted at Samudra University, Langsa City. The research subjects were students of chemical education at FKIP Samudra university. Data in this study were obtained through interviews and questionnaires. The questionnaire analysis technique was performed using a percentage formula and interpreted to determine the student character value categories. The results showed the average student character values ​​in the use of the lab module secondary metabolite utilization are 84% in the excellent category. Based on the statistical tests, sig. 0.00 showed that the character values ​​of students in the use of lab modules were on average above 50. The results of this study are expected to be information for researchers to develop integrated lab modules for character values.